2001
DOI: 10.1007/s001270170039
|View full text |Cite
|
Sign up to set email alerts
|

The experience of caregiving for severe mental illness: a comparison between anorexia nervosa and psychosis

Abstract: Carers of people with anorexia nervosa are challenged by the difficulties their role produces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
226
2
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(246 citation statements)
references
References 6 publications
11
226
2
7
Order By: Relevance
“…Parents' level of anxiety and strain when their child has severe AN, and their need for support, may easily be underestimated. 46 Our results indicate that both parents found it valuable to be involved in their child's treatment, by staying with her during hospitalization and participating in family therapy sessions. The high level of parental satisfaction with family therapy in adolescent AN is consistent with the studies of Krautter and Lock 12 and Paulson-Karlsson et al 14 In Norway, parents are entitled to sick leave with full salary to care for severely ill children under the age of 18.…”
Section: Resultsmentioning
confidence: 68%
“…Parents' level of anxiety and strain when their child has severe AN, and their need for support, may easily be underestimated. 46 Our results indicate that both parents found it valuable to be involved in their child's treatment, by staying with her during hospitalization and participating in family therapy sessions. The high level of parental satisfaction with family therapy in adolescent AN is consistent with the studies of Krautter and Lock 12 and Paulson-Karlsson et al 14 In Norway, parents are entitled to sick leave with full salary to care for severely ill children under the age of 18.…”
Section: Resultsmentioning
confidence: 68%
“…This finding is consistent with other research suggesting that family caregivers of individuals with EDs experience significant burden of care. 58 Fourth, research further suggests that the impact of EDs on patients' HRQOL is substantial and comparable to other serious illnesses and disorders. In addition to reporting that patients with AN and BN reported lower HRQOL than healthy control patients, Keilen et al 49 also found that patients with ED were impaired at a level comparable to or greater than patients awaiting coronary surgery for angina, candidates for heart/lung transplantation, and patients selected for heart transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that caring for someone with an eating disorder carries a significant burden, taking a toll on the health and well-being of the caregivers. [15][16][17] Individuals caring for those with AN have been found to have higher levels of distress than those caring for people with psychoses. 17 Specific challenges related to an eating disorder involve the carers' emotional response to the illness, the serious consequences of the illness, the detrimental effects of the illness on family members, and self-blame regarding the condition.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Individuals caring for those with AN have been found to have higher levels of distress than those caring for people with psychoses. 17 Specific challenges related to an eating disorder involve the carers' emotional response to the illness, the serious consequences of the illness, the detrimental effects of the illness on family members, and self-blame regarding the condition. 15,18,19 In light of the current state of the research, the purpose of this study was to examine the influence of living with a child with a potentially life threatening and chronic medical condition on family relationships.…”
Section: Introductionmentioning
confidence: 99%